Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702536
|View full text |Cite
|
Sign up to set email alerts
|

Ethermap

Abstract: Real-time synchronization is increasingly available in webbased environments for editing textual data, and this has changed how groups of people collaborate. We present a novel approach for real-time collaborative editing of geo-data. We introduce Ethermap, an open source webapplication that implements this approach and enables multiple users to map data concurrently. It supports synchronous and collaborative mapping in several ways: it visually highlights mapping activities, it allows for fine-grained reviewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Evaluations of multi-scale navigation need to identify effective and ineffective uses of these interfaces. Therefore, terms like the level of details or the visible extent are translated into a computational model, which is used to calculate an analytic solution for optimal animations (Furnas and Bederson, 1995). These models can be tested via user experiments that include free parameters like animation speed.…”
Section: Multi-scale Navigationmentioning
confidence: 99%
“…Evaluations of multi-scale navigation need to identify effective and ineffective uses of these interfaces. Therefore, terms like the level of details or the visible extent are translated into a computational model, which is used to calculate an analytic solution for optimal animations (Furnas and Bederson, 1995). These models can be tested via user experiments that include free parameters like animation speed.…”
Section: Multi-scale Navigationmentioning
confidence: 99%
“…With the development of computer technologies such as cloud computing and real-time communication, computer-supported collaborative work has become more and more important and has received extensive attention in recent years. CSCW [16][17][18][19][20] has been extensively studied and has been widely used in codesign [3][4][5][6] and editing [7,[18][19][20]. There are some industrial applications available in the network, such as Google Drive and SharedJS, which are used to help people in different locations share information and collaborate with each other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tools that enable collaborative authoring, particularly ones that allow simultaneous multi-user interactions, have captured the interests of researchers in diverse domains, including software engineering [12,38,40,46,113,119], data science [72,90,102,116,117,123], document editing [39,55,57,65,109], entertainment [69,98], and geospatial analysis [29], many of whom observed novel or unforeseen issues arise from the collaborative features. For example, Goldman et al built a collaborative, web-based Java IDE called Collabode [40], but found upon evaluation that programmers' code produced runtime errors for collaborators despite it being free of compilation errors.…”
Section: Multi-user Collaborative Authoring Toolsmentioning
confidence: 99%